DEVELOPING JOURNAL HISTORY (JOURY) THROUGH PROJECT BASED LEARNINGAS TEACHING MEDIA FOR TEACHING SOCIAL SCIENCES IN GRADE VOF ELEMENTARY SCHOOLS - Titik Nur Istiqomah; Fani Akdiana; Agma Dian Kartika (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
This research was aimed at developing instructional media for social sciencesbased on Project Based Learning for the fifth grade students of elementary schools.The material was chosen based on the Content Standards of Elementary School inwhich history was the dominant material in the fifth grade.The method used in this research was RD (Research and Development). Thesteps were (1) finding the problem, (2) collecting data, (3) designing the product, (4)validating the design, (5) revising the design, (6) experimenting the product, (7)revising the product, (8) using the experiment, (9) revising the product. The mediadeveloped was puzzle. The puzzle was developed into a journal to make the instructionmore interesting for the students. The experiment included thirty students fromGiwangan State Elementary School on Wednesday, 24th July 2013.The result of the research showed the relation between the media and theinstruction method of Project Based Learning and the effectiveness of the media. Thelearning process was carried out based on lesson plans. The result of the observationshowed that the students achieved the average of 3.67. The data then being convertedto qualitative data were classified into a good category.